Inequalities in child health care in Pakistan: measurement and decomposition analysis of maternal educational impact. (June 2020) - Asif, A.M.; Akbar, M.
Abstract: Objectives: The aim of the study was to measure the impact of maternal education on inequalities in child health care and to explore the contribution of different factors to the observed inequality. Study design: The study is based on secondary data from the Pakistan Demographic and Health Survey 2017–18. Methods: Concentration curves and indices were used to identify and quantify the inequality in child health care. Moreover, contributions of different factors to the observed inequality were investigated using decomposition analysis. Results: The concentration indices for health care provided were 0.078 ( P  < 0.001) when a child was experiencing diarrhoea and 0.088 ( P  < 0.001) for fever/cough. The results of this study indicate that healthcare practices are more common among children of educated mothers. The main contributors resulting in the observed inequalities in child health care were improved sanitation (about 6% for diarrhoea and 15% for fever/cough treatment), rural residence (about 4% and 23% for diarrhoea and fever/cough treatment, respectively), wealth status (49% and 28% for diarrhoea and fever/cough treatment, respectively) and maternal education (26% for diarrhoea and 28% for fever/cough treatment). Conclusion: The findings suggested that child health care is more frequently provided among educated mothers; therefore, steps should be taken to improve maternal education. Moreover, policies should seek to increase/improve the roles of women in society, as well as job opportunities to overcome the financial barriers of healthcare provision. Highlights: This study contributes to the international and Pakistani literature by quantifying the extent of educational inequality regarding child health care. The study demonstrated the contributions of different factors, through decomposition analysis, to the observed inequality. Maternal education plays a vital role in child care during illness. Through this study, the policymakers have an opportunity to discuss the impact of maternal education on the child health care. In addition, continuous monitoring of healthcare access is needed by the policymakers.